Life, death and fossilization on Gran Canaria: Implications for Macaronesian biogeography and molecular dating - Anderson, Cajsa Lisa (2009)
The Canaries have recently served as a test-bed island system for evaluating newly developed parametric biogeographical methods that can incorporate information from molecular phylogenetic dating and ages of geological events. To use such information successfully, knowledge of geological history and the fossil record is essential. Studies presenting phylogenetic datings of plant groups on oceanic islands often through necessity, but perhaps inappropriately, use the geological age of the oldest island in an archipelago as a maximum-age constraint for earliest possible introductions. Recently published papers suggest that there is little chance of informative fossil floras being found on volcanic islands, and that nothing could survive violent periods of volcanic activity. One such example is the Roque Nublo period in Gran Canaria, which is assumed to have caused the extinction of the flora of the island (c. 5.3-3.7 Ma). However, recent investigations of Gran Canaria have identified numerous volcanic and sedimentological settings where plant remains are common. We argue, based on evidence from the Miocene-Pliocene rock and fossil records, that complete sterilization of the island is implausible. Moreover, based on fossil evidence, we conclude that the typical ecosystems of the Canary Islands, such as the laurisilva, the Pinus forest and the thermophilous scrubland, were already present on Gran Canaria during the Miocene-Pliocene. The fossil record we present provides new information, which may be used as age constraints in phylogenetic datings, in addition to or instead of the less reliable ages of island emergences or catastrophic events. We also suggest island environments that are likely to yield further fossil localities. Finally, we briefly review further examples of fossil floras of Macaronesia.